Human Resource Management Strategy at SMP Sains Wahid Salahuddin Wahid Bintan - Arzun Septian; Via Riani; Aisha Dolisti Maulina; Nadia Vega; Satriadi Satriadi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to explore the implementation of human resource management strategies at SMP Sains Salahuddin Wahid Bintan. The study used a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The research sample consisted of the principal and two staff members of SMP Sains Salahuddin Wahid Bintan. The results of the study indicate that human resource management at the school has succeeded in integrating Islamic values ​​into modern management practices. The recruitment process not only considers professionalism but also the morals and personality of prospective teachers/staff. The selection is carried out collectively by a team consisting of the principal, academic coordinator, and senior teachers. Performance assessment is carried out through direct supervision and evaluation in monthly meetings. Aspects assessed include discipline, teaching creativity, classroom management, and contribution to the development of school programs.